PERSEPSI MASYARAKAT TERHADAP OBJEK WISATA BANDAR BAKAU, DI KELURAHAN PANGKALAN SESAI, KECAMATAN DUMAI BARAT, KOTA DUMAI - Febriani, Putri; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The past few years tourist destination become familiar and be an indicator of community economic development. Almost in every region be extract and expand natural tourism  especially, by show various beauty and preservation which be the magnet, like mangrove port. Mangrove port is conservation place which saved from development planning for harbor’s expansion. With every effort to save, finally mangrove port can be maintained. Later the headway directed be tourism destination, which very worthwhile for society’s life around. But, the things make society’s perception, positive perception as well as negative perception. The perception appear be adapted with phenomenon and impact which arise in society’s environment. This research is quantitative research with descriptive type. Population and sample from this research is people from RT.05 in Kelurahan Pangkalan Sesai with taking sample  by Slovin and get 74 respondent. Data collected by field observation, interview with make questionnaire first, and documentation. Analysis is done by processing data in groups in every indicator and cross tabulation. Conclusion from this research is society’s perception with tourism attraction mangrove port which in postive way make positive response from respondent. While negative perception appear from negative response from respondent. As is mangrove port impact to social’s life and economic growth in society. Various changes occur like increase economic people because increased income. Create collaboration between society, manager, and government agency because mangrove port. Key words: Mangrove port, Perception, Impact.